Creating volume estimates for buried shell deposits: A comparative experimental case study using ground‐penetrating radar (GPR) and electrical resistivity under varying soil conditions. Issue 2 (8th February 2018) - Kenady, Selene L.; Lowe, Kelsey M.; Ridd, Peter V.; Ulm, Sean
Abstract: Sampling issues represent a persistent problem in shell matrix research, particularly for large shell deposits. When small samples are taken from large buried deposits it is almost impossible, under current research practices, to understand how representative that sample is of the overall deposit. This case study tests a novel method for creating a better understanding of the buried deposits from which excavated samples are taken, thereby allowing for improved sampling strategies and a better understanding of how representative those samples are of the overall site. The case study employs two geophysical survey methods, ground‐penetrating radar (GPR) and electrical resistivity, to investigate buried shell deposits under experimental conditions. The survey results were used to create volume estimations and three‐dimensional (3D) models of buried shell deposits. This method is novel to shell matrix research and the current case study was designed to test the viability of the method under differing conditions. As well as testing the two geophysical methods, surveys were conducted under different moisture levels, soil types and survey transect spacings. Results showed that the 3D models and volume estimates of the deposit were successful in creating a representative understanding of the nature of the buried deposit, but with varying degrees of accuracy. GPR results created more accurate volume estimates and 3D models than the electrical resistivity results. Both geophysical methods produced more accurate results under drier conditions, though the electrical resistivity produced more visually distinct results with higher moisture levels. Analysis of the volume results revealed an error margin (to a confidence level of 95%) of 9.5% ± 15.5% for the GPR, and 44.5% ± 31.5% to 56 ± 70.5% for the electrical resistivity, depending on the interpretation method used to create the models.